The power of coaching in the professional learning and development of school leaders: an ecological framework and critical insights from a systematic review - Ciarán Collins; Regina Murphy; Martin Brown (Frontiers in Education, 2025)
School leadership has been shown to have a profound influence on students’ experiences and outcomes. Following the success of leadership coaching in industry, coaching has started to feature as a mechanism in the professional learning and development of school leaders. However, to date, evidence of how the various elements of coaching are embedded in the professional learning and development of school leaders is limited. To fill the lacuna of research in this area, this study aimed to conduct a systematic literature review of coaching as a form of the professional learning and development of school leaders, based on papers published in peer-reviewed journals between July 2014 and July 2024. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were used, and the work was framed within Bronfenbrenner’s ecological systems theory. An overview of the concept of coaching and its development in the context of the professional learning and development of school leaders was provided. The methodology used in the study was then described, before the research evidence on coaching in the professional learning and development of school leaders was reported and discussed across five thematic findings, illuminating the factors that may advance the success of coaching as well as those that may impede it. Gaps in the literature were identified that may inform further research on this important topic.